Political communication in the digital environment. Evaluation of interactivity strategies of European think tanks - Castillero-Ostio, Elizabet; Moreno-Cabanillas, Andrea; Serna-Ortega, Álvaro (Universidad de Alicante, 2025)
Think tanks, as social and political actors, have achieved an undeniable global influence on political decisions and the formation of public opinion. This study allows us to understand the digital communication, through official websites, of European think tanks in their relations in the virtual environment. The study sample consists of the 25 most influential Western European think tanks, based on the 2020 Global Go To Think Tank Index Report (McGann, 2021). Through a quantitative content analysis, the communicative tools of the websites of these organisations were examined, as well as the level of interactivity they provide. The results show that the unidirectional tools in most frequent use include graphic displays (information brochures or presentation spaces of the think tank and images and photographs) and the use of tools that enable a greater degree of interactivity. In terms of bidirectional tools, asymmetric ones predominate, such as subscription forms for content syndication, a web search system, file downloads and tools or buttons for sharing on social networks or sending information to external sites. Across the board, the research highlights the need for think tanks to move towards two-way online models to improve relations with their audiences.
Keywords: Comunicación en política; Medios de comunicación social - Aspectos políticos; Europe; Think tanks; Digital communication; Political communication; Interactivity